2019
DOI: 10.2514/1.c035452
|View full text |Cite
|
Sign up to set email alerts
|

Passive Gust Loads Alleviation in a Truss-Braced Wing Using an Inerter-Based Device

Abstract: This paper presents a novel method for gust loads alleviation in a truss-braced wing in which an inerter-based device located in the truss-structure is used to reduce peak-loads during a discrete '1-cosine' gust. Three candidate layouts are considered and the device parameters are optimised to target the response of the first three structural modes. It is demonstrated that either a single damper or a combination of inerter-based devices can be used to achieve a reduction of approximately 4% for spanwise locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The University of Bristol Ultra-Green (BUG) cantilevered wing design was inspired by the strut-supported highaspect-ratio wing of the NASA SUGAR Volt aircraft configuration [30], with the main aim of studying the nonlinear aeroelastic effects associated with large wing deflections [9,31,32]. The BUG half-wing FEM model (48564 degrees of freedom) has a span of 25.89m and is shown in Fig.…”
Section: B Representative Gfem Of a High-aspect-ratio Wingmentioning
confidence: 99%
“…The University of Bristol Ultra-Green (BUG) cantilevered wing design was inspired by the strut-supported highaspect-ratio wing of the NASA SUGAR Volt aircraft configuration [30], with the main aim of studying the nonlinear aeroelastic effects associated with large wing deflections [9,31,32]. The BUG half-wing FEM model (48564 degrees of freedom) has a span of 25.89m and is shown in Fig.…”
Section: B Representative Gfem Of a High-aspect-ratio Wingmentioning
confidence: 99%
“…Here, it is shown that the maximum relative velocity is achieved during the 9m gust. This is because the short gusts have the largest bandwidth [38], meaning that they excite the higher frequency modes of the structure which, generally speaking, are truss-dominated modes. Furthermore, due to the higher bandwidth of the short gusts the excitation frequency is much larger which gives a higher velocity and acceleration for a given displacement.…”
Section: Gust Response Of the Baseline Aeroelastic Modelmentioning
confidence: 99%
“…For the model considered in this study, it appears that the jury-strut is an inappropriate location for a device that influences the behaviour of the outboard bending mode. It is possible that a rotational device co-located at the strut-wing joint, as in [38], would provide better performance in terms of alleviating the outboard bending.…”
Section: B Tuned-inerter-dampermentioning
confidence: 99%
“…Recently, it has been proposed that the truss could serve not simply as static support, but also to reduce dynamic gust loads by inserting a vibration absorber into one of the struts, either as a traditional suspension system [5], or as an inerter-based device [6]. The geometric nonlinearities stemming from the greater flexibility associated with HAR wings, however, mean that the traditional modelling methods, based on linear elastic and aerodynamic theory, are not necessarily adequate, and can lead to conservative structural designs [7], and to inaccurate estimations of the flutter speeds [3,8].…”
Section: Introductionmentioning
confidence: 99%